Changes Of The Blood-Brain Barrier Permeability, Ultrastructure, And Protein And Gene Expressions In A Rat Model Of Cerebral Hypoperfusion - Sekaran, Hema (2019)
Cerebral hypoperfusion is a condition where there is reduced blood flow to the brain. This condition is observed in patients with cardiovascular diseases, hypertension and among the aging population. Cerebral hypoperfusion leads to more severe neurological diseases including vascular dementia, Alzheimer’s disease and multiple sclerosis. Cerebral hypoperfusion induces damages to the blood-brain barrier (BBB) and this detailed study was carried out to understand the BBB behavior during cerebral hypoperfusion. In this study, two-vessel occlusion (2VO) model was used to mimic cerebral hypoperfusion in rats. Using exogenous tracers of different molecular weight i.e. Evans blue dye (69 kDa) as a marker for macromolecule leakage, and sodium fluorescein (376 Da) as a marker for small molecule leakage, BBB leakages to Evans blue dye was observed during the early phase of cerebral hypoperfusion, 1-day post-surgery in the brain regions frontal cortex, posterior cortex and thalamus-midbrain. Using transmission electron microscopy, vesicles and formation of fenestration in endothelial cells, and swelling of astrocyte end-feet were observed, indicating cellular damages leading to BBB leakages during cerebral hypoperfusion.